A Linguistic Analysis of Emoji’s: Exploring the Role of Language in the Digital Age of Generation Z - Un Nisa, Sarwat (Journal of Natural Language and Linguistics, 2024)
This study investigates young adults’ use of emoticons (emojis) in India, focusing on their effectiveness in digital communication. It aims to understand factors influencing their use and their potential impact on social inclusion, using a quantitative approach and a structured questionnaire to understand the factors driving emoji usage. The study’s major results indicate that intention to use emojis during virtual communication is significantly influenced by factors such as accuracy, sociability, enjoyment, and efficiency, which together account for 16.4% of the variance. The most significant factor among them is sociability, as respondents agreed that emojis make online communication more social and interactive. The results will aid in comprehending the significance and utility of emojis and how their use can facilitate effective virtual communication among users. The study proposes a statistically significant model to determine the usage and effectiveness of emojis as a new form of digital communication.